(untitled) (Journal of Engineering, 2023)
Buildings begin to deteriorate gradually over time due to several factors, including environmental influences, improper use of the building, and neglected repairs for damages during the building’s life span. Effective maintenance practices can minimize operational costs, extend the life of building systems and components, improve energy efficiency, and maintain property value. This paper aims to review articles related to building maintenance to identify factors affecting maintenance practices. After conducting the review, the result was that there were 33 factors affecting building maintenance categorized into six groups: management-related factors, manpower-related factors, technical-related factors, financial-related factors, building user-related factors, and building characteristics-related factors. Facility managers can enhance their understanding of building maintenance by examining the various factors that affect maintenance. By doing so, they can assess how these factors affect maintenance practices. This evaluation is crucial as it assists in creating efficient maintenance plans while optimizing resource allocation and timely repairs. Moreover, this approach enables facility managers to adopt proactive strategies toward maintenance, ultimately leading to cost savings by addressing or managing potential obstacles hindering optimal building maintenance.